Implications of primary tumor site and fraction size on outcomes of palliative radiation for osseous metastases - McDougall, Riley P.; Ho, Quoc-Anh; Hsu, Charles; Robbins, Jared R. (Frontiers in Oncology, 2025)
PurposeThis study reviewed palliative radiation therapy (RT) practices and outcomes and compared the percentage of remaining life spent receiving RT (PRLSRT) in patients treated for osseous metastases.MethodsA retrospective analysis was conducted using the National Cancer Database (2010–2016) to evaluate metastatic patients who received palliative bone RT. Common palliative RT schemes were analyzed to determine treatment patterns and outcomes. Palliative outcomes, including median PRLSRT, RT completion, and mortality rates, were calculated. Binary logistic regression was performed to identify factors affecting RT completion, and a scoring system was developed to identify patients at risk for poor palliative outcomes.ResultsA total of 50,929 patients were included, with the majority diagnosed with NSCLC (45.2%), breast cancer (15.1%), or prostate cancer (10.8%). The median overall survival after palliative RT was 5.74 months. Patients receiving lower doses per fraction (2.5 Gy/Fx) tended to be younger, healthier, and yet experienced worse palliative outcomes. Binary logistic regression identified age, race, income quartile, and Gy/Fx as significant factors affecting RT completion. Median PRLSRTs were as follows: 14.95% for GI NOS, 9.89% for upper GI, 9.46% for NSCLC, 8.67% for skin, 7.06% for SCLC, 6.10% for lower GI, 5.59% for GYN, 5.44% for GU, 5.35% for HNC, 2.05% for endocrine, 2.03% for prostate cancer, and 1.82% for breast cancer. Patients receiving 2.5 and 3 Gy/Fx were less likely to complete RT compared to those receiving 4 Gy/Fx (OR, 1.429 and 3.780, respectively; p < 0.001). Age, comorbidities, primary tumor, target location, and metastatic burden were associated with PRLSRT ≥ 25%.ConclusionDose regimens and patient selection influence palliative bone RT outcomes. Both factors should be carefully considered to minimize the burden of care and maximize treatment benefits.